Anti-salusin-β antibody enhances angiogenesis after myocardial ischemia reperfusion injury. (September 2013) - Masumura, Mayumi; Watanabe, Ryo; Nagashima, Ayako; Ogawa, Masahito; Suzuki, Jun-ichi; Shichiri, Masayoshi; Komuro, Issei; Isobe, Mitsuaki
<x xml:space="preserve">Abstract</x> Backgrounds: Salusins are multifunctional endogenous bioactive peptides simultaneously biosynthesized from their precursor prosalusin. Salusin-β stimulates proliferation of vascular smooth muscle cells and fibroblasts and regulates myocardial growth and hypertrophy. Salusin-β has potent hypotensive, bradycardic and proatherosclerotic effects. Objectives: To investigate whether salusin-β plays a role in myocardial remodeling after myocardial ischemia reperfusion (I/R) injury, rat I/R models were created by the left anterior descending coronary artery occlusion for 30 min, followed by 24 h or 7 days of reperfusion (control, n = 6 each). Results and Conclusion: Immunohistochemical double staining showed the enhanced expression of salusin-β in the macrophages around myocardial ischemic area. Anti-salusin-β treated groups were administered the neutralizing salusin-β antibody (10 μl/day, i.p.) once daily from day −1 to day 1 or from day −1 to day 7 (anti-salusin-β, n = 6 each). The anti-salusin-β therapy enhanced myocardial angiogenesis in the peri-ischemic area of reperfusion. The small vessels (< 40 μm in diameter) of I/R hearts treated with anti-salusin-β were more densely populated than those of control animals (108.5 ± 19.7 vs 47.5 ± 2.4, p < 0.05). Real-time PCR revealed that the anti-salusin-β therapy-induced angiogenesis was not associated with enhanced vascular endothelial growth factor A expression. The authors, for the first time, have clarified that endogenous salusin-β suppresses angiogenesis which is critical in the development of cardiac remodeling following I/R injury.